Arylamine N-acetyltransferase activity in human cultured cell lines. - Coroneos, E (1993)
Many arylamine and hydrazine drugs and xenobiotics are acetylated by liver N-acetyltransferase (NAT; EC 2.3.1.5). Two loci, mnat and pnat, encode the enzymes designated monomorphic and polymorphic NAT (mNAT and pNAT) respectively. These isoenzymes have different substrate specificities. In addition, at the polymorphic locus a diversity of alleles is found, which differ by specific point mutations that may or may not result in amino acid substitutions. These point mutations result in the 'slow' acetylation of substrates of pNAT. The substrates for NAT include carcinogenic arylamines. Susceptibility to bladder cancer has been related to slow acetylation. NAT has been characterized in immortalized human cell lines to assess their use in studies of the metabolism or arylamines in vitro. A monocytic cell line (U937) and two hepatoma cell lines of parenchymal lineage (HepG2 and Hep3B) have been shown to catalyse acetylation of substrates of mNAT but do not acetylate sulphamethazine, a substrate specific for pNAT. Using PCR to amplify the alleles of pNAT, followed by restriction-enzyme digestion of the product, the cell lines have been genotyped: U937 cells are homozygous slow acetylators (S1a/S1a) and HepG2 cells are heterozygous slow acetylators (S1a/S2). Transcription of pnat was confirmed in the hepatoma cell lines, by amplification of cDNA generated from these cells. In addition, splicing of mRNA specific for pNAT has been demonstrated by using a primer which anneals to a region in the 5' promoter region. Unlike the hepatoma cell lines, in U937 cells the pNAT gene is not transcribed. However, transcription of mnat was shown to occur in all three cell lines.